Targeting Tau protein novel PET imaging agent and preparation method thereof - DOU XIAOFENG; WANG JING; ZHANG HONG; JIN CHENTAO; XU YANGYANG; YU CONGCONG; ZHONG YAN (2024)
The invention discloses a novel PET (Polyethylene Terephthalate) imaging agent for targeting Tau protein and a preparation method of the novel PET imaging agent, and the novel PET imaging agent is recorded as [18F] FENPBM and has the following structural formula; the compound can be used as a positron emission tomography (PET) tracer, can be combined with Tau protein with high specificity in a living body, provides key image information in the aspects of early diagnosis, disease progress monitoring, curative effect evaluation, pathological research and the like, and has wide clinical and research application prospects. # imgabs0 # 本发明公开了一种靶向Tau蛋白的新型PET显像剂及其制备方法，记为[18F]FENPBM，具有如下结构式；该化合物能够作为正电子发射断层成像(Positron Emission Tomography,PET)示踪剂，能够在活体内高特异性地结合Tau蛋白，提供早期诊断、疾病进展监测、疗效评估及病理研究等方面的关键影像信息，具有广泛的临床和研究应用前景。#imgabs0#